2023
DOI: 10.3389/fpsyg.2023.1143827
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and implications of pro-nature physical activity in antagonizing psychological stress: the key role of microbial-gut-brain axis

Abstract: Appropriate physical activities and a biodiversity-rich environment are conducive to the relief of psychological stress, and pro-nature physical activities are a combination of the two, which has good application potential in antagonizing psychological stress, but the intervention mechanism is still unclear. The microbiota-gut-brain axis is cyclically associated with psychological stress, and psychological stress can affect the microbiota through the gut-brain pathway, and conversely, the microbiota can also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 115 publications
(118 reference statements)
0
4
0
1
Order By: Relevance
“…Lou found that combining structured physical activity with a lifestyle that fully exposes people to nature, or “pro-nature physical activity”, can effectively improve the “physical and mental comorbidities” of patients with DGBIs ( 194 ). This “green prescription” not only embodies the medical treatment concept from a holistic viewpoint, but also provides a new perspective and means for treating diseases related to stress and psychological disorders ( 195 ).…”
Section: New Treatment Strategies For Ibd Based On the Brain-gut-micr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Lou found that combining structured physical activity with a lifestyle that fully exposes people to nature, or “pro-nature physical activity”, can effectively improve the “physical and mental comorbidities” of patients with DGBIs ( 194 ). This “green prescription” not only embodies the medical treatment concept from a holistic viewpoint, but also provides a new perspective and means for treating diseases related to stress and psychological disorders ( 195 ).…”
Section: New Treatment Strategies For Ibd Based On the Brain-gut-micr...mentioning
confidence: 99%
“…Moreover, physical activity can reduce visceral fat content and the expression of proinflammatory factors (such as TNF-α and IL-6) and increase intestinal mucosal immunity, epithelial integrity, and tissue regeneration. Among them, pro-nature physical activity can regulate the MGBA; increase the abundance of Firmicutes and Akkermansia bacteria; increase SCFAs levels; and further affect the HPA axis, BDNF, and serotonin pathways involved in bidirectional gut-brain communication, thereby maintaining body homeostasis and reducing psychological stress ( 194 ).…”
Section: New Treatment Strategies For Ibd Based On the Brain-gut-micr...mentioning
confidence: 99%
See 1 more Smart Citation
“…It justifies the need to find and develop methods for correcting stress-induced disorders of the digestive system. The alimentary canal is characterized by high reactivity to stressors of various natures, including increased intestinal permeability [50,51]. The result of increased intestinal barrier permeability is the uncontrolled invasion of antigens, microorganisms and toxic substances from the lumen of the intestine into the mucous membrane, which, in turn, can cause inflammatory and other reactions [52][53][54].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%
“…В даний час проблема впливу стресу різної етіології на стан кишкової мікробіоти та гомеостаз слизової оболонки травного каналу, є одним з актуальних питань біологічної і морфологічної науки, і обґрунтовує необхідність пошуку і розробки методів корекції стрес-індукованих порушень системи травлення. Травний канал характеризується високою реактивністю щодо впливу стресорів різної природи, у тому числі -у вигляді підвищення проникності кишечника [50,51]. Наслідком підвищення проникності кишкового бар'єру є неконтрольована інвазія антигенів, мікроорганізмів і токсичних речовин з просвіту кишки вглиб слизової оболонки, що, у свою чергу, може спричинити розвиток запальних та інших реакцій [52][53][54].…”
Section: огляди літератури / Literature Reviewsunclassified